Evaluation of Growth Performance in Sinyonya Carp (Cyprinus carpio L.) Fed with varying inclusion levels of Indigofera - Agung, Lukman Anugrah; Hermawan, Dodi; Massie, Rudy Taufik Putra (Jurnal Biologi Tropis, 2024)
Carp is a valuable freshwater fish that thrives in various temperatures and water conditions, making it suitable for cultivation in diverse regions to satisfy community needs for animal protein. However, one of the primary challenges in carp farming is the high cost of commercial feed, which can contribute up to 91.2% of total production expenses. Thus, identifying affordable alternative protein sources is essential. Indigofera zollingeriana, a protein- and amino acid-rich plant, shows potential as an alternative to traditional feed ingredients like soybean meal. This study examines the effectiveness of using Indigofera as a feed ingredient for Sinyonya carp (Cyprinus carpio). The research applied a Completely Randomized Design with 5 treatment groups, each with varying Indigofera zollingeriana concentrations: TDI 0, TDI 25, TDI 50, TDI 75, and TDI 100. Findings revealed that Indigofera-based feed significantly boosted absolute growth and daily growth rate of the fish, although it did not influence feed efficiency or survival rate. The optimal concentration was determined to be TDI 75, or 75% Indigofera. Water quality remained favorable for the fish throughout the study.